Faktor-Faktor Mempengaruhi Remitan Migran Sumatera Barat yang Bekerja pada Sektor Informal di Kota Palembang - Nyayu Tiyara Wahyuni; Bambang Bemby Subiyakto; Happy Warsito (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2017)
This study aims to analyze the factors that affect remittances and utilization of migrants from West Sumatra who work in the informal sector in the city of Palembang. This study was conducted in Palembang City with a population of 1232 people. Of the population of 1232 people, taken samples through proportional stratified random sampling method, then obtained a sample of 92 migrant respondents from West Sumatra. Data analysis was done by using multiple regression method in order to measure how big the independent variable is income, the number of family dependent, the existence of nuclear family, the length of permanent migrants, the frequency of remittance delivery, the remittance means that affect the dependent variable that is remittance. Simultaneously (together) income variables, the number of family dependents, the presence of nuclear families, the length of permanent migrants, the frequency of remittance delivery, remittance means significantly influence the remittances of migrants from West Sumatra working in the informal sector in Palembang City. It is known that partially long migrants remain, the frequency of remittance remittances, remittance means not significantly affect the remittance of migrants from West Sumatera working in informal sector in Palembang City means remittance based on the length of permanent migrant, remittance frequency, remittance means no difference. Income, the number of family dependents, the existence of nuclear families significantly affect the remittances of migrants from West Sumatra who work in the informal sector in Palembang City.